INOVASI BANK SAMPAH PERAMPUAN HEBAT DENGAN PENDEKATAN EKONOMI SIRKULAR KELOLA ORGANIC WASTE MENJADI PRODUK EKONOMI KREATIF - Zaenafi Ariani (Bajang Institute, 2023)
Several issues that are interesting and integrated with courses and the industrial world are related to the environment and waste with a circular economy approach. The results of the 2021 campus and city waste research show that the type of food and drink most often consumed on campus and in households in the form of packaged rice dominates 65.8% and plastic packaging 49.4% (Nurjannah S, 2021). The high percentage of these types of food and beverages has an impact on the generated waste. The waste generated by the campus is a scourge in health and environmental aspects. Efforts to encourage a circular economy transition in Indonesia to achieve sustainable development or Sustainable Development Goals (SDGs). The circular economy will take on a bigger role, especially in relation to the increasing commitment to zero waste within the Muhammadiyah University of Mataram campus environment, and in the future it can realize zero waste West Nusa Tenggara. Therefore, circular economy is the most appropriate model in waste management. In 2022, we are likely to see a stronger push for the transition to a circular economy in anticipation of the climate crisis.